Perkembangan Penelitian Good Corporate Governance dalam Perspektif Agency Theory di Indonesia: (Systematic Literature Review Tahun 2020–2025) - Davina Syafanisa Hermansya (Journal of Management and Creative Business, 2026)
Research on Good Corporate Governance (GCG) in Indonesia has continued to grow, covering various topics such as firm value, financial performance, earnings management, and financial statement fraud prevention. This study aims to identify the development, trends, and research gaps in GCG studies from the perspective of Agency Theory in Indonesia during the 2020–2025 period. This study employed a Systematic Literature Review (SLR) using the PRISMA framework. A total of 37 articles that met the inclusion criteria were analyzed using thematic analysis. The findings indicate that Agency Theory remains the most widely adopted theoretical framework, with the most frequently examined GCG mechanisms being independent commissioners, audit committees, and institutional ownership. Existing studies are predominantly concentrated in state-owned enterprises, banking, and manufacturing sectors, while the findings regarding the effect of GCG on earnings management and financial statement fraud remain inconsistent. This study recommends expanding future research to small and medium-sized enterprises (SMEs) and startups, as well as adopting mixed-method approaches and incorporating digital governance aspects.